Comparative characteristics of genre modifications of internet-portals - Rassyhovich Gazizov, Ramis; Anvarovna Bakeeva, Diana (Opción, 2019)
The study aims to investigate the comparative characteristics of genre modifications of internet-portals via comparative analysis and system-functional methods. In the article, it is shown that online editions focus attention on accurate positioning of the media activity, find all groups of the potential visitors of the website: the factor of the audience becomes for them the leader together with such typological signs as the essence of information, frequency of online publications. The conducted research is drawn that Internet portals help to be guided better in social processes, comprehensively satisfying information need.